Surface quality and biocompatibility of porous hydroxyapatite scaffolds for bone tissue engineering. Issue 5 (27th February 2013) - Wu, Bin; Braun, Anne; Ediger, Simon; Huang, Wei; Lilischkis, Rainer; Schäfer, Karl‐Herbert; Wu, Quan; Zhang, Xianglin; Saumer, Monika
Abstract Surface quality and biocompatibility were critical properties of bone scaffolds. Fabrication and biological properties of porous hydroxyapatite (HA) scaffolds made by extrusion deposition method (EDM) and microwave sintering were investigated in this paper. The scaffolds with side length of 3.61 mm, height of 0.51 mm, pore size of 139 µm, Ra of 1.67 µm, and Rmax of 10.5 µm were used as substrates for osteosarcoma cells (SAOS 2) culturing to investigate the scaffolds' biological properties. Surface metrology and morphology before and after cell culture were measured to approach the interaction of cell culture with the scaffolds. The results showed that the HA scaffolds made by EDM had good biocompatibility and the surface metrology of scaffolds does not have an obvious change under cell culture even for 21 days. SAOS‐2 could attach to and grew well on scaffolds even after culturing for 21 days. And Ra and Rmax of scaffolds surfaces were 1.67 ± 0.59 µm and 10.5 ± 3.9 µm before cell culture and 1.64 ± 0.62 µm and 10.6 ± 4.5 µm after cell culture. EDTA have significant influences upon the HA grains, and the cells themselves also seem to lead to subtle scaffold degradation.